The Effectiveness of Project-Based Learning Model and Assessment of Learning Outcomes Against Portfolio - Retnaningsih, Retnaningsih; Ridlo, Saiful; W.H, Nugrahaningsih (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
A total of 25% of 38 teacher in SMP Negeri 10 Semarang conducted a portfolio assessment. Observation results obtained attitudes and low process skills. Learning achievement of new motion system material is 44% complete Minimum Mastery Criteria (KKM) 75%. Alternative learning models used to overcome these problems are project-based learning (PjBL) with portfolio assessment. The purpose of this study was to analyze the completeness of attitude, science process skills, improvement of learning achievement, and differences in learning achievement of students in the material of the motion system with PjBL models using portfolio assessment. The design of this study was Pretest and posttest control group design. Completeness of attitudes, skills, learning achievements were analyzed by the proportion of one party. Improved learning achievement with the N gain test. Anava 1 way is used to see the difference between the two learning achievement scores of Experiment Groups 1, 2 and Control. Independent t-test is used to see Learning Achievement Levels for Experiments Groups 1 and 2. The results showed that: (1) the attitudes of the experimental class students reached completeness asan 63 (72.79) with a percentage of 81.26%; (2) the science process skills of the experimental class students reached completeness ≥ 63 (70.83) with a percentage of 90.63%; (3) Learning achievement results are stated to be completed individually with a value of ≥ 71 (mean 79.28) and classical with ≥ 80% (84.38%); Learning achievement in the motion system material with PjBL model using portfolio assessment increases with N-gain of 0.65 (moderate); (4) F count > F table (6,699> 3,094), so Ho is rejected, so there is significant differences between experimental class 1, experimental class 2, and control; (5) the value of t count < t table (1.165 <1.998) then Ho is accepted, which means that there is no significant difference between the experimental group 1 and experiment 2.